2019
DOI: 10.12944/crnfsj.7.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Ready - to - Eat Food from Dhaka, Bangladesh

Abstract: The objective of this research was to assess the microbiological quality of ready-to-eat food available in Dhaka city, Bangladesh, and check the risk factors associated with ingestion of ready-to-eat food from popular public places. This study was conducted in the Center of Excellence in the Department of Microbiology, Primeasia University, Dhaka, Bangladesh from August 2016 to February 2017. Forty-five samples belonging to 18 categories were collected aseptically in triplicates in pre-sterilized zip-lock bags… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…For the widespread human consumption of poultry meats and eggs, the control of microbial contamination is necessary [3]. Poor hygiene, sanitation and poor to nonexistent microbiological monitoring are major contributing factors for various type of food born infection as well as promoting the growth of harmful drug-resistant pathogens in them [4,5]. Food poisoning and intoxications caused by microorganisms each year cause severe repercussion to public health along with economic losses of related industries and personnel.…”
Section: Introductionmentioning
confidence: 99%
“…For the widespread human consumption of poultry meats and eggs, the control of microbial contamination is necessary [3]. Poor hygiene, sanitation and poor to nonexistent microbiological monitoring are major contributing factors for various type of food born infection as well as promoting the growth of harmful drug-resistant pathogens in them [4,5]. Food poisoning and intoxications caused by microorganisms each year cause severe repercussion to public health along with economic losses of related industries and personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published many study on food samples claim that ready to eat foods of Bangladesh were contaminated with different microorganisms, among them E. coli was predominantly present in most of the cases (35). Present study found that, all the samples were contaminated with heterotrophic bacteria within the range of 10 4 to 10 6 cfu/g (Table 1).…”
Section: Resultsmentioning
confidence: 47%
“…in foods including meat (poultry), milk and milk products (both raw and pasteurized) [23,44], eggs [21,22], vegetables, ready to eat or street food (singara, lemon juice, fuska, sugarcane juice, borhani etc.) [20,37,40] and vegetables [36]. In addition, across all categories of sampling, E. coli and Salmonella spp.…”
Section: Resistance Pathogen Originated From Human Foodmentioning
confidence: 99%